2021
DOI: 10.1111/jerd.12859
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of thin wall endodontically treated teeth without ferrules restored with various techniques

Abstract: Objective To evaluate the fracture resistance and failure characteristics of simulated thin wall endodontically treated teeth without ferrules restored with various techniques. Materials and methods Forty‐eight human mandibular single‐root canal premolars were decoronated and endodontically treated. The 1 mm thick remaining root canal dentin was prepared. The roots were randomly divided into four groups of 12 roots according to the following post and core reconstruction techniques: direct resin composite post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…In 2018, a systematic review by Nauman et al reported that in clinical situations where there are no remaining coronal structures, no consensus or definitive finding supports or rejects the use of posts. 7 However, an in vitro study by Iemsaengchairat and Aksornmuang 38 demonstrated that in the cases where ETT have thin remaining root walls and a complete absence of a ferrule, cast metal posts and cores provided the highest fracture resistance, followed by multiple fiber posts and composite resin cores.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a systematic review by Nauman et al reported that in clinical situations where there are no remaining coronal structures, no consensus or definitive finding supports or rejects the use of posts. 7 However, an in vitro study by Iemsaengchairat and Aksornmuang 38 demonstrated that in the cases where ETT have thin remaining root walls and a complete absence of a ferrule, cast metal posts and cores provided the highest fracture resistance, followed by multiple fiber posts and composite resin cores.…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple fiber post technique in comparison to a single FRC posts has shown better results. 6 21…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple fiber post technique in comparison to a single FRC posts has shown better results. 6,21 Post diameter has a great influence on post stiffness, but its effect on fracture resistance is yet to be researched. According to some studies, posts with larger diameters are recommended since they have demonstrated higher resistance than less diameter posts, but this is not as important as saving the tooth structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiff materials can promote high stress concentrations in the post surface but will deflect less during loading, which can be better to support the coronal restorations. However, this can result in catastrophic fractures of roots in weakened areas if overloaded with occlusal forces [ 15 , 16 , 17 ]. In clinical protocols, some materials were tested to prevent the catastrophic fractures of endodontically treated teeth [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%